Decision Support System for Tourism Supply Chain Strategy in Banyumas Regency - Uscha, Cindy Malinda; Pranindyasari, Chelsia (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
Tourism is a sector that consistently supported by the government due to its impact on Indonesia's economic growth. One of the regions with the highest number of tourist attractions in Central Java is Banyumas Regency, known especially for its natural tourism. However, tourism growth in Banyumas has stagnated and even worse having a drecreased due to the impact of COVID-19. To accelerate economic recovery through tourism, the government has implemented various efforts, including strengthening the supply chain process from upstream to downstream. However, Banyumas has not yet optimized the supply chain process, resulting with amount of visitor are less than the tourism attraction that offered in Banyumas. This study aims to determine supply chain strategies for enhancing tourism growth in Banyumas Regency. Using SWOT analysis initially, followed by the Analytical Hierarchy Process (AHP) for prioritizing strategies, the results suggest that the optimal strategy is a Strength-Opportunity (SO) approach, focusing on developing affordable, family tour packages for natural tourism destination, cultural festivals, and art events through village tourism.